Pemanfaatan Lahan Pekarangan Untuk Budidaya Sayuran Organik di Desa Kediri Kabupaten Banyumas - Indah Setiawati; Rosi Widarawati; Pepita Haryanti; Okti Herliana (Jurnal Ilmiah Pangabdhi, 2021)
The science and technology application activities are planned to be carried out with the partner of the women farmer group located in Kediri Village, Karanglewas District. The problems faced by partners are not having adequate knowledge about natural pest management and the correct use of organic fertilizers; do not have skills in making and using vegetable pesticides, liquid organic fertilizers, and proper organic vegetable cultivation techniques. The purpose of applying science and technology is to provide knowledge about the functions and ways of using vegetable pesticides and liquid organic fertilizers, improving skills in making and using vegetable pesticides, POC, technical complete package of organic vegetable cultivation. Methods for achieving the goal are socialization and learning by doing, which are complemented by guiding and piloting techniques. The output of the service activities is in the form of articles in dedication journals, and articles on appropriate technology (TTG).